PSYCHOMETRIC PROPERTIES AND FACTORIAL STRUCTURE OF LEARNING DISABILITY SCALE WITHIN THE PALESTINIAN CONTEXT - Shtawi, Rania (An-Najah National University, 2025)
This study investigates the psychometric properties and factorial structure of the Learning Disabilities Evaluation Scale – Fourth Edition (LDES-4) within the Palestinian context. The scale comprises 88 items distributed across seven subscales: listening, thinking, speaking, reading, writing, mathematics, and memory. The scale was translated into Arabic and culturally adapted to ensure its suitability for use in the Palestinian educational environment. The study sample consisted of 400 individuals residing in the West Bank, selected through stratified random sampling from five educational districts: Nablus, Hebron, Qalqilya, Jenin, and Tulkarm. The scale was administered to teachers (resource room, Arabic language, and mathematics) through direct communication and professional group distribution. The findings revealed that the LDES-4 demonstrates strong psychometric properties in the Palestinian context. Exploratory factor analysis identified four primary factors that reinforced the overall construct validity of the scale. High correlation coefficients and reliability indices were recorded, with Cronbach’s alpha values ranging between 0.841 and 0.984, indicating a high degree of internal consistency and scientific validity. Moreover, no statistically significant differences were found in participants’ responses based on gender, age, or geographic location, which affirms the stability of the scale across demographic groups. The subscales related to mathematics and spelling exhibited relatively higher difficulty levels compared to those of thinking and speaking. These results underscore the reliability and validity of the LDES-4 as an effective tool for diagnosing learning disabilities, supporting its application in educational assessment and strategic planning. The study recommends the broader use of the scale for evaluating learning difficulties among Palestinian students and suggests the development of training programs for teachers and special education professionals on its administration and interpretation to ensure best practices in the identification and diagnosis of learning disabilities.
الخصائص السيكومترية والبناء العاملي لمقياس صعوبات التعلم ضمن السياق الفلسطيني